HIV Injection Risk Behaviors among HIV-Negative People Who Inject Drugs Experiencing Homelessness, 23 U.S. Cities. Issue 1 (2nd January 2022) - Marcus, Ruthanne; Cha, Susan; Sionean, Catlainn; Kanny, Dafna; ,
ABSTRACT: Despite recent declines in numbers of people who inject drugs (PWID) diagnosed with HIV, clusters of HIV among PWID are ongoing, especially among PWID experiencing homelessness. Using data from the National HIV Behavioral Surveillance in 2018, we evaluated the association between homelessness and injection risk and prevention behaviors among HIV-negative PWID who were recruited by respondent-driven sampling in 23 U.S. cities. Interviewers assessed sociodemographic characteristics, history of overdose, and behavioral risk and prevention factors for HIV. Adjusted prevalence ratios (aPR) and 95% CI were obtained using Poisson regression models. Of 10, 614 HIV-negative PWID participants, 7275 (68.5%) reported experiencing homelessness. Homeless PWID were more likely than those who were not to be younger age, white, unemployed, without health insurance, in poverty, experiencing psychological distress, and incarcerated in the past 12 months. PWID experiencing homelessness were significantly more likely to report injection risk behaviors [share syringes/equipment (aPR = 1.26; 95% CI = 1.20–1.33), non-fatal opioid overdose (aPR = 1.64; 95% CI = 1.49–1.79)] and prevention behaviors [testing for HIV in past 12 months (aPR = 1.18; 95% CI = 1.12–1.24) and using syringe services programs (aPR = 1.09; 95% CI = 1.03–1.16)] than PWID not experiencing homelessness. Homelessness among PWID is associated with injection risk behaviors and non-fatal overdose.